CuGeO3 hollow nanotubes and preparation method and application thereof
The preparation of CuGeO3 hollow nanotubes through electrospinning and heat treatment solves the problems of low efficiency of Coulomb and rapid attenuation of reversible capacity during charging and discharging of lithium-ion battery negative electrode materials, achieving high lithium storage capacity and good cycle stability.
Patent Information
- Application Number
- CN202310380296.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-03-31
AI Technical Summary
The existing lithium-ion battery anode materials are inefficient during charging and discharging, and their reversible capacity is rapidly attenuated. The Ge-based materials are prone to agglomeration and form thick SEI films during the lithium embedding process, resulting in structural damage and high costs.
CuGeO3 hollow nanotubes were prepared by two-step electrospinning and heat treatment. The preparation method of Cu-Ge precursors was used, including dissolving polyvinylpyrrolidone in a mixed solvent of N,N-dimethylformamide and anhydrous ethanol, adding copper acetate dihydrate and tetraethoxygermanium, electrospinning and baking, and then heat treatment was performed to form CuGeO3 hollow nanotubes.
The prepared CuGeO3 hollow nanotubes exhibit high lithium storage capacity, good cycle stability and excellent rate performance in the negative electrode materials of lithium-ion batteries, alleviating the mechanical pressure of Ge-based materials during volume expansion and contraction, and improving the structural stability of the material.
Smart Images

Figure CN116553601B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanotube preparation, and in particular to a CuGeO3 hollow nanotube and a preparation method and application thereof. Background Art
[0002] Currently, the negative electrode material of commercial lithium-ion batteries (LIBs) is graphite. However, the theoretical capacity of graphite is only 372 mAh g -1 This value is difficult to meet the demand for energy storage systems of the rapidly developing electronic devices. Therefore, the industry is in urgent need of designing and developing new high-capacity LIBs electrode materials. Among them, alloy materials Si and Ge have theoretical capacities of 4200mAh g -1 and 1624mAhg -1 The high theoretical capacity has led to the extensive research of this type of material by scientific researchers, who are committed to replacing graphite with it. + The diffusion rate is 400 times that of metallic Si, and the electronic conductivity of Ge is 104 times that of Si. Therefore, Ge-based materials have become a research hotspot for LIBs electrode materials. However, the distribution of metallic Ge is limited, and the cost of Ge-containing raw materials is relatively high. In addition, similar to Si materials, Ge-based materials have a volume expansion rate of nearly 300% during the charge and discharge cycle, which can easily cause pulverized damage to the structure of the electrode material itself and cause the active material to fall off the electrode sheet. Moreover, metallic Ge is prone to agglomeration during the lithium insertion process and forms a thick SEI film. These unfavorable factors will ultimately lead to low Coulomb efficiency of Ge-based materials and rapid attenuation of reversible capacity.
[0003] Researchers have proposed a variety of methods to solve the above problems. First, the preparation of nanostructured Ge can slow down the mechanical stress changes suffered by Ge during lithium insertion and de-lithiation, and at the same time increase the active sites for contact between the electrolyte and the material; among them, the one-dimensional (1D) nanostructure can be closely connected to the current collector, increasing the Li + Transmission dynamics, relieving stress changes, these advantages have aroused great research interest among scientific researchers. Secondly, hybridizing Ge materials with carbon to form Ge / C composites can alleviate the volume expansion of metal Ge during the alloying process and increase the structural stability of Ge materials; thirdly, preparing porous Ge materials, the porous structure is conducive to the penetration of electrolytes, and at the same time shortens the Li + and e -The transmission distance at the contact interface between the electrode and the electrolyte. Finally, the metal Ge is compounded with other electrochemically active metals M to form Ge-based metal oxides, which can not only increase the capacity of Ge-based materials, but also reduce the Ge content in the material, thereby reducing the cost of raw materials to some extent. At the same time, the atomic array formed between the active metal M and Ge can provide a buffer space for each other and increase the structural stability of the material. Therefore, it is urgent to find a simple, mass-produced preparation method to prepare Ge-based 1D structured nanomaterials. Summary of the invention
[0004] One of the technical problems to be solved by the present invention is to provide a method for preparing CuGeO3 hollow nanotubes to solve the problem that conventional preparation methods are difficult to mass produce and have complicated steps.
[0005] To solve the above problems, the present invention provides a method for preparing CuGeO3 hollow nanotubes, comprising the following steps:
[0006] S1: Preparation of Cu-Ge precursor:
[0007] S11: dissolving polyvinyl pyrrolidone in a mixed solvent of N,N-dimethylformamide and anhydrous ethanol to form a clear solution;
[0008] S12: adding cupric acetate dihydrate and tetraethoxygermanium to the clear solution, and stirring to a homogeneous solution;
[0009] S13: transferring the homogenous solution into a syringe for electrospinning, and peeling off the obtained Cu-Ge-PVP;
[0010] S2: Preparation of CuGeO3 hollow nanotubes:
[0011] S21: heating the Cu-Ge-PVP to 200° C. and baking it in an air atmosphere to obtain a Cu-Ge-PVP precursor;
[0012] S22: heat-treating the Cu-Ge-PVP precursor, the heat treatment process includes: heating the Cu-Ge-PVP precursor at a heating rate of 1°C / min, heating it to 350°C for the first time, keeping it warm for the first time, and then heating the Cu-Ge-PVP precursor to 500-700°C for the second time at a rate of 1°C / min after keeping warm. After the second time keeping warm, CuGeO3 hollow nanotubes are obtained.
[0013] In the preparation method of the CuGeO3 hollow nanotube of the present invention, in the selection of metal raw materials, copper acetate is selected as the copper source, and acetate anions have better compatibility in organic solvents than copper chloride, and acetate decomposes to form CO2+H2O in the later heat treatment process, which is conducive to pore formation in the fiber; tetraethoxygermanium is selected as the germanium source, and organic germanium has good compatibility in organic solvents, which is conducive to forming a clear and uniform electrospinning solution. The tetraethoxygermanium cannot be exposed to water, otherwise it will be hydrolyzed to form a white solid, which is not conducive to the complete dissolution of the germanium source.
[0014] In the selection of solvents, a mixed solvent of N,N-dimethylformamide (DMF) and anhydrous ethanol is selected, wherein the ratio of DFM to anhydrous ethanol can be between 1:1 and 2:1. However, pure DMF or pure anhydrous ethanol is not acceptable; and the homogeneous solution used as the spinning solution must be prepared and used immediately, otherwise it is easy to gel, which is not conducive to the spinning process.
[0015] The method for preparing CuGeO3 hollow nanotubes of the present invention includes pre-oxidation in step S21 and heat treatment in step S22 in the heat treatment step for preparing the CuGeO3 hollow nanotubes, so that the CuGeO3 hollow nanotubes can be prepared better.
[0016] As a preferred solution, in step S11, the average molecular weight of the polyvinyl pyrrolidone is 360,000, the mass concentration of polyvinyl pyrrolidone in the clear solution is 12%, and the average molecular weight of the polyacrylonitrile is 150,000.
[0017] As a preferred solution, in step S11, the molar ratio of N,N-dimethylformamide to anhydrous ethanol is (1-2):1.
[0018] As a preferred solution, in step S12, the molar ratio of cupric acetate dihydrate to tetraethoxygermanium is 1:1.
[0019] As a preferred solution, in step S13, the electrospinning step includes: injecting the homogenized solution into a plastic syringe, equipped with a No. 7 stainless steel needle, placing a receiving aluminum foil on a receiver 15 cm below the needle, and pushing at a speed of 1 mL h -1 , voltage was 15 kV, and electrospinning was performed.
[0020] As a preferred solution, in step S13, the mass concentration of polyvinyl pyrrolidone in the homogeneous solution is 9-13%.
[0021] As a preferred scheme, in the step S21, the temperature rise is a step-by-step temperature rise, including: heating the Cu-Ge-PVP to 100°C, keeping it warm for 2 hours, then heating it to 150°C, keeping it warm for 5 hours, then heating it to 170°C, keeping it warm for 5 hours, and finally heating it to 200°C; the baking time is 24 hours.
[0022] As a preferred solution, in step S22, the temperature of the second heating is 500°C, and the time of the first insulation and the second insulation is 3 hours.
[0023] By adopting the above-mentioned step-by-step heating method, the pre-oxidation temperature of S21 is controlled so that the pre-oxidation time is 12 hours. If the time is too short, it is not conducive to maintaining the fiber structure during heat treatment. Through the heat treatment of S22, the heating rate is controlled at 1°C / min and 350°C is maintained for 3 hours to ensure that the polymer additive is fully decomposed, and then the temperature is continued to be raised for calcination.
[0024] One of the technical problems to be solved by the present invention is to provide a CuGeO3 hollow nanotube to solve the problem of low coulombic efficiency and rapid attenuation of reversible capacity of conventional materials during charge and discharge.
[0025] In order to solve the above problems, the present invention provides a CuGeO3 hollow nanotube, characterized in that: the CuGeO3 hollow nanotube is prepared by the preparation method described in any one of claims 1-8.
[0026] Another technical problem to be solved by the present invention is to provide an application of the above-mentioned CuGeO3 hollow nanotubes, which includes applying the above-mentioned CuGeO3 hollow nanotubes to the negative electrode material of a lithium-ion battery, thereby solving the problem of low coulombic efficiency and rapid attenuation of reversible capacity of conventional materials during charging and discharging.
[0027] The present invention prepares CuGeO3 hollow nanotubes by a two-step method of electrospinning and heat treatment. When used as LIBs electrode materials, after the first discharge of the CuGeO3 nanotubes, the in-situ formed CuO and Ge nanoparticles show a synergistic lithium storage effect, which not only promotes the product to have a high lithium storage capacity, but also helps Ge to relieve mechanical pressure during volume expansion and contraction. Therefore, the CuGeO3 hollow nanotubes prepared by the present invention show excellent performance in terms of specific capacity, cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD and FE-SEM images of Cu-Ge-PVP precursor, where (A) and (B) are XRD and FE-SEM graphs, respectively;
[0029] Figure 2 TGA and DSC graphs of Cu-Ge-PVP precursor and XRD and XPS graphs of CuGeO3 hollow tube, where (A) is TGA and DSC graphs of Cu-Ge-PVP precursor; (B) is XRD graph of CuGeO3 hollow tube, (C), (D), (E), (F) are XPS graphs;
[0030] Figure 3 FE-SEM, TEM, HRTEM, TEM mapping and EDS images of CuGeO3 hollow tubes, where (A) and (B) are FE-SEM images, (C), (D) and (E) are TEM images, (F) is a HRTEM image, the inset is a SAED image, (G), (H), (I) and (J) are TEM mapping images, and (K) is an EDS image;
[0031] Figure 4 XRD and FE-SEM images of Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600, wherein (A) is the XRD image of Cu-Ge-300, (B) and (C) are the FE-SEM images of Cu-Ge-300; (D) is the XRD image of Cu-Ge-400, (E) and (F) are the FE-SEM images of Cu-Ge-400; (G) is the XRD image of Cu-Ge-600, and (H) and (I) are the FE-SEM images of Cu-Ge-600;
[0032] Figure 5 TGA curves of Cu-Ge-300, Cu-Ge-400, Cu-Ge-500 and Cu-Ge-600;
[0033] Figure 6 BET and pore size distribution diagrams of Cu-Ge-500, Cu-Ge-300, Cu-Ge-400, and Cu-Ge-600, wherein (A), (B), (C), and (D) are BET and pore size distribution diagrams of Cu-Ge-500, Cu-Ge-300, Cu-Ge-400, and Cu-Ge-600, respectively;
[0034] Figure 7 For Cu-Ge-500, Cu-Ge-300, Cu-Ge-400, Cu-Ge-600 at 0.1A g -1 The following cycle diagrams show that (A), (B), (C), and (D) are Cu-Ge-500, Cu-Ge-300, Cu-Ge-400, and Cu-Ge-600 at 0.1A g -1 The following circular line chart;
[0035] Figure 8The electrochemical performance data of Cu-Ge-300, Cu-Ge-400, Cu-Ge-500 and Cu-Ge-600. Among them, (A) is the electrochemical performance data of Cu-Ge-500 at 0.1A g -1 Voltage-specific capacity curves of the first five cycles. (B) is the CV curve of Cu-Ge-500, and (C) is the CV curve of Cu-Ge-300, Cu-Ge-400, Cu-Ge-500, and Cu-Ge-600 at 0.1 A g -1 The lower cycle diagram (D) is Cu-Ge-500 in 0.5Ag -1 and 1.0A g -1 (E) is the rate performance diagram at different current densities, (F) is the EIS diagram of Cu-Ge-300, Cu-Ge-400, Cu-Ge-500, and Cu-Ge-600 after cycling; (G) is the EIS diagram of Cu-Ge-500 at 2.0A g -1 The electrical performance diagram after 1000 cycles;
[0036] Fig. 9 The cycle line diagram and CE diagram of the LiFePO4 / CuGeO3 full battery at 0.1C, where (A) is the structural schematic diagram of the LiFePO4 / CuGeO3 full battery, (B) and (C) are the voltage-specific capacity and specific capacity-cycle diagrams of the LiFePO4 / CuGeO3 full battery at 0.1C. (D) is the rate performance diagram of the LiFePO4 / CuGeO3 full battery at different current densities. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present invention provides a method for preparing a CuGeO3 hollow nanotube, comprising the following steps:
[0039] S1: Preparation of Cu-Ge precursor:
[0040] S11: dissolving polyvinyl pyrrolidone or polyacrylonitrile in a mixed solvent of N,N-dimethylformamide and anhydrous ethanol to form a clear solution;
[0041] S12: adding cupric acetate dihydrate and tetraethoxygermanium to the clear solution, and stirring to a homogeneous solution;
[0042] S13: transferring the homogenous solution to a syringe for electrospinning, and stripping the resulting Cu-Ge-PVP from a receiver;
[0043] S2: Preparation of CuGeO3 hollow nanotubes:
[0044] S21: heating the Cu-Ge-PVP to 200° C. and baking it in an air atmosphere to obtain a Cu-Ge-PVP precursor;
[0045] S22: heat treating the Cu-Ge-PVP precursor, wherein the heat treatment process comprises: heating the Cu-Ge-PVP precursor at 1°C min -1 The Cu-Ge-PVP precursor is heated at a heating rate, the first heating is heated to 350°C, and the first heat preservation is performed. After the heat preservation, the Cu-Ge-PVP precursor is heated to 500-600°C at a rate of 1°C / min for the second time. After the second heat preservation, CuGeO3 hollow nanotubes are obtained. In order to further study the effect of calcination temperature on the morphology and composition of the final product, the present invention conducted experiments with different calcination temperatures (300, 400, 500 and 600°C), and the products were named Cu-Ge-300, Cu-Ge-400, Cu-Ge-500 and Cu-Ge-600 respectively;
[0046] Preferably, in step S11, the molecular weight of the polyvinyl pyrrolidone is 360,000, the mass concentration of polyvinyl pyrrolidone in the clear solution is 12%, and the molecular weight of the polyacrylonitrile is 150,000.
[0047] Preferably, in step S11, the molar ratio of N,N-dimethylformamide to anhydrous ethanol is (1-2):1.
[0048] Preferably, in step S12, the molar ratio of cupric acetate dihydrate to tetraethoxygermanium is 1:1.
[0049] Preferably, in step S13, the electrospinning step comprises: injecting the homogenized solution into a plastic syringe, equipped with a No. 7 stainless steel needle, placing a receiving aluminum foil on a receiver 15 cm below the needle, and pushing at a speed of 1 mL / h -1 , voltage was 15 kV, and electrospinning was performed.
[0050] Preferably, in step S13, the mass concentration of polyvinyl pyrrolidone in the homogeneous solution is 9-13%.
[0051] Preferably, in step S21, the temperature increase is a step-by-step temperature increase, including: heating the Cu-Ge-PVP to 100°C, keeping it warm for 2 hours, then heating it to 150°C, keeping it warm for 5 hours, then heating it to 170°C, keeping it warm for 5 hours, and finally heating it to 200°C; the baking time is 24 hours.
[0052] Preferably, in step S22, the temperature of the second heating is 500° C., and the time of the first insulation and the second insulation is 3 hours.
[0053] The present invention also provides a CuGeO3 hollow nanotube, which is prepared by the preparation method.
[0054] The present invention also provides an application of a CuGeO3 hollow nanotube, which includes applying the CuGeO3 hollow nanotube to a negative electrode material of a lithium ion battery.
[0055] The following provides examples combining data and tests for preparing products to carry out detailed development of the above scheme of the present invention:
[0056] S1: Preparation of Cu-Ge precursor:
[0057] S11: a certain amount of polyvinylpyrrolidone (PVP, average molecular weight of 360000) is dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and anhydrous ethanol to form a clear solution with a PVP mass fraction of 12%.
[0058] S12: Subsequently, 1 mmol of copper acetate dihydrate (Cu(Ac)2·2H2O) and 1 mmol of tetraethoxygermanium (Ge(OET)4) were added to the above clear solution and magnetically stirred to a homogeneous solution.
[0059] S13: The obtained solution is transferred into a plastic syringe and equipped with a No. 7 stainless steel needle. The receiving aluminum foil is placed on the receiver 15 cm below the needle, with a propulsion speed of 1 mL h-1 and a voltage of 15 kV. After a period of spinning, the obtained Cu-Ge-PVP is peeled off from the aluminum foil.
[0060] S2: Preparation of CuGeO3 hollow nanotubes:
[0061] S21: heating Cu-Ge-PVP in stages: heating the Cu-Ge-PVP in an air atmosphere in a tube furnace in stages, specifically to 200° C. (24 h), to obtain a Cu-Ge-PVP precursor;
[0062] S22: Control the heating rate: 1°C / min to heat the Cu-Ge-PVP precursor to 350°C and maintain for 3 hours, then heat to 500°C at 1°C / min and maintain for 3 hours to obtain CuGeO3 hollow nanotubes.
[0063] The above-mentioned CuGeO3 hollow nanotubes were subjected to relevant tests:
[0064] Structural characterization:
[0065] Structural characterization: The composition and phase purity of the product were tested using Bruker's D8 Advance, with the operating voltage set to 40 kV and the operating current set to 40 mA. X-ray photoelectron spectroscopy (XPS) was tested on an ESCALAB 250 spectrometer. The product morphology was tested on a Hitachi S-4800SEM field emission scanning electron microscope (FE-SEM), and the elemental energy X-ray spectrum (EDS) quantitative analysis was performed on a spectrometer attached to the Hitachi S-4800SEM. Transmission electron microscopy images (TEM), high-resolution transmission images (HR-TEM) and selected area electron diffraction patterns (SAED) were all tested on a high-resolution transmission electron microscope (TEM, JEM-2100), and the elemental energy spectrum distribution (mapping) diagram was tested on the spectrometer attached to the TEM. Thermogravimetric analysis (TGA-DSC) of the sample was performed on a synchronous thermal analyzer, model DTG-60AH, the test atmosphere was air, and the heating rate was 10 °C min -1 The specific surface area (Brunauer-Emmett-Teller, BET) of the samples was measured on a BELSORP-MAX specific surface area and pore structure analyzer. The pore size distribution was obtained by fitting the Barrett-Joyner-Halenda (BJH) model.
[0066] Electrochemical performance test:
[0067] The electrical test was carried out at room temperature using a CR2025 button cell on a blue electricity tester (CT2001A), with the operating voltage window set to 0.01-3.0V. The obtained active material (CuGeO3), acetylene black additive and binder sodium carboxymethyl cellulose (CMC) were mixed and ground in a mass ratio of 70:15:15, and deionized water (H2O) was added as a solvent to form a paste. The paste mixture was evenly applied on the copper foil and then dried at 120°C for 24h under vacuum conditions. After the punching and pressing process, the negative electrode material electrode sheet was obtained. The metal Li sheet was the counter electrode and the Celgard 2400 polymer film was the diaphragm. The electrolyte was a mixture of 1M LiPF6 dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1. The effective mass of the active material was 1.05mg cm-2 The battery assembly was carried out in a glove box, where the oxygen content and water content were both less than 1 ppm. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed on an electrochemical workstation (CHI660D), where the CV scan rate was 0.1 mV s -1 , the voltage window is 0.01-3.0V; the EIS test frequency range is 100KHz-0.01Hz.
[0068] The full battery assembly uses CuGeO3 as the negative electrode and commercial LiFePO4 as the positive electrode. The preparation process of the LiFePO4 positive electrode film is as follows: LiFePO4, acetylene black, and PVDF are mixed and ground in a mass ratio of 8:1:1, and NMP solvent is added to form a paste and evenly applied on aluminum foil. Dry at 120°C in a vacuum for 24 hours. The assembly of the full battery requires that the positive and negative electrode materials have a 1:1 ratio, and the negative electrode capacity is slightly greater than the positive electrode. In this paper, the mass ratio of the positive electrode to the negative electrode is close to 1:4. Before the full battery assembly, CuGeO3 needs to be pre-lithiated to reduce the irreversible capacity loss in the initial cycle. The specific operation is to directly contact the metal Li with the negative electrode in the presence of the electrolyte for 30 minutes. Celgard 2400 polymer film is used as a separator. A mixture of 1M LiPF6 dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1 is used as the electrolyte. Full battery test at 0.1C (1C = 170mAh g -1 ) with an operating voltage window of 1.0-3.9 V and the reversible capacity calculated based on the mass of the positive electrode material.
[0069] Structural characterization of CuGeO3 hollow nanotubes:
[0070] First, the structure and chemical composition of the prepared product are detected by XRD. Figure 1 As shown in A, the Cu-Ge-PVP precursor has a broad peak at about 25°, and no other crystalline peaks appear, indicating that the precursor is an amorphous structure. Figure 1 B is the FE-SEM spectrum of the Cu-Ge-PVP precursor. It can be seen from the figure that the sample is composed of nanofibers with uniform particle size, smooth fiber surface, up to tens of microns in length, and a fiber size of about 400-500nm.
[0071] The present invention uses TGA-DSC to study the weight loss of Cu-Ge-PVP, such as Figure 2As shown in A, the part below 300℃ is the water adsorbed on the surface of Cu-Ge-PVP and the residual DMF solvent in the fiber, with a weight loss of 17.1%. The exothermic peak at 327.3℃ is due to the thermal decomposition of PVP; the strong exothermic peak at 366.9℃ belongs to the transformation and formation peak of CuGeO3. From 300-500℃, the whole process is accompanied by 87.0% weight loss, and there is almost no weight loss above 500℃. After heat treatment at 500℃ in air for 3h, the product is still close to amorphous structure ( Figure 2 B).
[0072] The present invention uses XPS to study the chemical composition of the product. Figure 2 As shown in C, only three elements, Cu, Ge, and O, appear in the full spectrum of the product. Figure 2 D is the high-resolution spectrum of Cu 2p, where 937.8eV represents Cu 2p1 / 2 and 966.73eV represents Cu 2p3 / 2, proving that Cu exists in the 2+ form; and 945.88eV and 958.47eV are the vibration peaks of Cu 2p1 / 2 and Cu 2p3 / 2. Figure 2 E is the Ge 3d high-resolution spectrum, and the two peaks at 31.4eV and 32.33eV are respectively attributed to Ge 2+ and Ge 4+ . Figure 2 F is the high-resolution spectrum of O1s. The four peaks at 530.2, 530.98, 531.8 and 532.74 eV represent lattice oxygen, oxygen in hydroxyl group and CO, OC=O and H2O respectively.
[0073] Figure 3 A and B are FE-SEM images of CuGeO3 hollow tube after heat treatment. It can be seen that CuGeO3 presents a one-dimensional fiber structure. From the high magnification FE-SEM ( Figure 3 B) shows that the nanofibers have an obvious hollow tubular structure and the fiber size is reduced to 200-250 nm, which is related to the decomposition of PVP and the phase transformation of CuGeO3 during the calcination process. The present invention uses TEM to further study the morphology of the product. Figure 3 As shown in C, the hollow structure of the fiber is obvious, which is consistent with FE-SEM. Figure 3 D, E) shows that the pore size is between 10-30nm, and the hollow tube wall is composed of particles of about 20-50nm. It can also be seen from the figure that there is no single particle in the fiber, and the fiber interior is an obvious hollow structure. HR-TEM spectrum ( Figure 3 F) shows no obvious lattice fringes, and the SAED spectrum ( Figure 3 F (inset) shows no obvious diffraction rings, proving that CuGeO3 is in an amorphous state, which is consistent with the XRD results. In addition, TEM maping and EDS images ( Figure 3 GK) shows that the three elements of Cu, Ge, and O are evenly distributed in the CuGeO3 hollow tube. The internal structure of the obtained fiber is highly hollow and porous. As a LIBs electrode material, it can provide more surface active sites and shorten the Li + and e - transmission path, thus improving the reversible capacity and increasing the cycle stability.
[0074] In order to further study the effect of calcination temperature on the morphology and composition of the final product, the present invention conducted experiments at different calcination temperatures (300, 400 and 600°C), named the products Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600, and studied their phases and morphologies. Figure 4 As shown in A, D, and G, with the increase of calcination temperature, the crystallinity of the product gradually increases. Specifically, the products Cu-Ge-300 and Cu-Ge-400 calcined at 300 and 400 °C show amorphous state ( Figure 4 A, 4D), increasing the calcination temperature to 600 ° C, the crystalline phase CuGeO3 (PDF card number is 32-0333) appears, and at the same time, amorphous carbon bulges of about 25° can be seen. The present invention uses TG ( Figure 5 ) analysis, calculated that the carbon content of the product obtained at 300 and 400 ° C was 72.7% and 7.9% respectively. Further increasing the calcination temperature to 500 and 600 ° C, there was no carbon in the product. The present invention studied the morphology of the above samples by FE-SEM, and it is obvious that Cu-Ge-300 ( Figure 4 B, C) are nanofibers with smooth surface and uniform particle size, while Cu-Ge-400 ( Figure 4 E, F), the fiber surface becomes rough, and hollow gaps can be seen in some fibers, showing a nanocable structure as a whole. Figure 4 H, I) maintains the hollow structure.
[0075] In order to study the pore structure properties of the product, the present invention conducted a N2 adsorption isotherm test on the product calcined at 300-600°C. Figure 6 As shown in the figure, it can be seen that from Cu-Ge-300 to Cu-Ge-600, the IV-type N2 adsorption curve gradually becomes obvious, proving the mesoporous characteristics of the material. Moreover, the pore size distribution range also changes from a single-peak mesoporous structure to a multi-peak graded mesoporous distribution. The tested specific surface area values are 5.99, 33.71, 42.16 and 29.55 m 2 g -1. From the data, the present invention can see that at 500°C, the specific surface area of the hollow tubular structure is the largest. The decomposition of PVP and the phase transformation of CuGeO3 during the calcination process are the main reasons for the formation of the fiber pore structure. Through the above characterization, the formation mechanism of CuGeO3 hollow nanotubes can be obtained, which specifically includes two aspects: the formation of the porous structure is due to the decomposition of PVP during the calcination process, and the void structure inside the hollow tube is due to the inward transfer of metal elements inside the fiber, while the metal elements outside the fiber diffuse outward rapidly to form the outer wall of the tube structure. In short, by simply adjusting the heat treatment temperature, the physical phase and morphology of CuGeO3 hollow nanotubes can be precisely controlled.
[0076] In view of the structural and morphological characteristics of the CuGeO3 hollow tube, the present invention makes it into a LIBs electrode material and studies its electrochemical performance. At the same time, as a comparison, the present invention also studies the cycle diagrams of Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600.
[0077] Figure 7 a is CuGeO3 hollow nanotubes in 0.1Ag -1 Cycle line diagrams of the 1st, 30th, 80th, 120th, and 150th cycles at current density, where the first discharge and charge capacities are 1295.6 and 1119 mAh g, respectively. -1 , the Coulombic efficiency (CE) is 86.4%. Figure 7 bd is Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600 in 0.1Ag -1 The cycle diagram below shows that the voltage platform length of the CuGeO3 hollow tube structure is much longer than that of the other three products. Figure 8 A is the voltage-specific capacity curve of the first five cycles of the CuGeO3 hollow tube. It can be seen that when lithium is inserted in the first cycle, the discharge capacity is about 482.6 mAh g above 1.0 V. -1 , below 1.0V, specific capacity is about 813.0mAh g -1 .and Figure 8 The CV curves of B are consistent. The curves of cycles 2-5 are highly overlapped, indicating that the lithium insertion and delithiation process is reversible. Figure 8 In B, during the first discharge process, the strong reduction peak at 1.06V is attributed to the decomposition of the CuGeO3 structure and some irreversible electrochemical reactions, including SEI film formation and electrolyte decomposition. The reduction peak below 0.5V corresponds to the alloying process between Li and Ge. Starting from the second cycle, the reduction peak at 1.33V is attributed to the multi-step reduction process from CuO to metallic Cu, mainly including CuO / Cu2O, Cu2O and the final Cu and Li2O phase changes. In the delithiation curve, 0.68V corresponds to Li xThe delithiation process of Ge alloy, 1.35V corresponds to the process of Cu being oxidized to CuO through multiple steps, and 1.89V corresponds to the secondary oxidation step of Ge. Starting from the second cycle, the CV curves overlap, indicating the reversible Li + Embedding and extraction process. Combining experimental data and literature reports, the present invention speculates that the lithium storage mechanism of CuGeO3 hollow tube is as follows:
[0078]
[0079]
[0080]
[0081]
[0082]
[0083] Figure 8 C is CuGeO3 hollow tubes, Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600 nanorods in 0.1Ag -1 Taking the CuGeO3 hollow tube as an example, the capacity loss in the first 30 cycles is mainly attributed to the formation of SEI film. From the 30th cycle onwards, the capacity is maintained well and there is a continuous upward trend. After 150 cycles, the reversible capacity is as high as 1605.6 mAh g -1 This data is much better than Cu-Ge-300 (717.8mAh g -1 ), Cu-Ge-400 (1033.8 mAh g -1 ) and Cu-Ge-600 (1025.5mAhg -1 ).like Figure 8 D, at 0.5Ag -1 After 150 cycles, the reversible capacity reaches 848.8 mAh g -1 , at 1.0Ag -1 After 150 cycles, the reversible capacity remains at 562.6 mAh g -1 And the CE has been maintained above 98%, proving that Li + The deintercalation process is highly reversible. Figure 8 E is the rate performance of the above materials, as shown in the figure, at 0.1, 0.2, 0.4 and 0.8Ag -1 Under the conditions of -1 Even when the current density is as high as 2.0 and 4.0A -1When the reversible capacity is still 597.7 and 423.5 mAh g -1 , and when the current density returns to 0.1Ag -1 When -1 , proving the good electrochemical reversibility of the material. At the same time, it can be seen from the present invention that the reversible capacity of the CuGeO3 hollow tube at each current density is higher than that of Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600. Figure 8 F is the EIS graph after the electrode cycle. It can be seen that after the cycle, the internal impedance data of the CuGeO3 hollow tube electrode is smaller than that of Cu-Ge-300, Cu-Ge-400 and Cu-Ge-600, indicating that it is more conducive to Li + and e - In addition, the present invention also makes the CuGeO3 hollow tube in 2.0Ag -1 A long cycle test of 1000 cycles was carried out under the following conditions. Figure 8 As shown in Figure 1, the lithium storage performance of the sample is stable. After 1000 cycles, the reversible capacity is as high as 631.8 mAh g -1 The data further demonstrate the reversibility of lithium storage in CuGeO3 hollow tubes at high current density.
[0084] After the above analysis, the present invention can draw the following conclusions: The excellent cycle and rate performance of CuGeO3 hollow tube is closely related to its unique composition and structure. First, the one-dimensional structure of CuGeO3 has the characteristics of high aspect ratio, which can increase the Li + The embedding speed is beneficial to improve the lithium storage performance. Secondly, during the first discharge process, the Ge nanoparticles formed in situ are highly uniformly distributed in the array formed by the two substances Li2O and Cu, which not only provides a buffer space for the volume expansion of Ge, but also effectively prevents the agglomeration of Ge nanoparticles. There are many opinions on the role of the in-situ formed Cu particles in the lithium storage process. The earliest Oh et al. pointed out that the Cu component in CuGeO3 will be converted into nano-scale metal Cu in situ during the initial lithium insertion process, and then maintain the metal Cu composition. Therefore, Cu only acts as a conductive network in the system to improve the conductivity of the Ge system. However, recent experimental data on many reports on CuO negative electrode materials have proved that during the lithium storage process, the formed Cu will react with Li2O to be converted into CuO, realize the reversible decomposition of Li2O, and improve the lithium storage capacity of the electrode material. In this chapter conclusion, the present invention can be seen that with the progress of the cycle, the reversible capacity gradually increases. Combined with the results of the literature, the present invention infers that in the CuGeO3 hollow tube, the Cu component is electrochemically active and can react reversibly with Li2O, promoting the conversion of Li2O with low electrochemical activity into Li +, and provide additional capacity, resulting in a gradual increase in reversible capacity as the cycle progresses. This can also be verified from the cyclic voltammetry (CV) curve. When used as a negative electrode for LIBs, the CuGeO3 hollow tube decomposes into Cu and Ge during the first discharge process, and Li 4.4 Ge is converted to Ge, and Cu is converted to Cu2O. Both Ge and Cu2O serve as storage sites for Li, which makes CuGeO3 have a high lithium storage capacity. Moreover, the in-situ formed Cu accelerates the e - transfer, thus enhancing the Li storage kinetics of the material.
[0085] In order to further verify the application potential of the material in the actual production of LIBs, the present invention uses CuGeO3 hollow tube as the negative electrode and commercial LiFePO4 as the positive electrode material to assemble a full battery. Fig. 9 A is a schematic diagram of the structure of the LiFePO4 / CuGeO3 full battery. Fig. 9 B is the cycle line diagram at 0.1C, which is the 1st, 50th, 100th, 150th and 200th cycles, where the working voltage window is 1.0-3.9V, and the reversible capacity is calculated based on the positive electrode mass. The first charge capacity and discharge capacity are 116.2 and 114.1 mAh g, respectively. -1 , the coulombic efficiency reaches 98.2%. In the subsequent cycles, it can be seen that the cycle curves are well matched, proving that the lithium storage process is reversible. In addition, through the cycle curves, it can be seen that the charge and discharge voltage platform gradually moves to a low voltage. The exact reason for this phenomenon is still unknown, but combined with previous literature reports, the present invention speculates that this is closely related to the changes in the hollow tube structure of CuGeO3 and electrochemical polarization during the cycle. Fig. 9 C is the cycle diagram and the corresponding CE diagram. It can be seen that after 200 cycles, the reversible capacity is maintained at 107.3 mAh g -1 , the capacity retention rate reached 99.5%, which is equivalent to an average decrease of 0.034% per cycle, proving the cyclic stability of the material. In addition, the CE has been stable above 99%, proving that the LiFePO4 / CuGeO3 full battery has high Li + Cycle efficiency. Fig. 9 D is the rate data of the full battery. It can be seen that the full battery has a good specific capacity retention rate after 0.05C to 4.0C and then back to 0.05C. From the above results, it can also be seen that the LiFePO4 / CuGeO3 full battery has high reversible capacity, good cycle stability, and stable CE value, indicating that the CuGeO3 hollow tube has practical application potential in the field of LIBs.
[0086] The present invention prepares CuGeO3 hollow nanotubes by combining electrospinning and heat treatment. During the heat treatment, polyvinyl pyrrolidone decomposes and generates gas, forming a porous structure in the fiber, and the hollow structure is the result of the outward diffusion of metal elements on the fiber surface and the inward diffusion of metal elements inside the fiber during high-temperature calcination. -1 After 130 cycles, the reversible capacity is as high as 1605.6 mAh g -1 The rate performance is also improved. After the first discharge, CuGeO3 decomposes, and the CuO formed in situ can not only serve as a lithium storage body, but also react with Li2O to release excess Li + , providing additional lithium storage capacity. In addition, the formed Cu nanoparticles accelerate the e - Transfer, enhance its rate performance. Moreover, the mesoporous hollow tube structure can effectively relieve the mechanical pressure of Ge during volume expansion and contraction, and enhance the structural stability. When used as LIBs electrode material, CuGeO3 nanotubes show excellent performance in specific capacity and cycle stability.
[0087] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing CuGeO3 hollow nanotubes, characterized in that: The following steps are involved: S1: Preparation of Cu-Ge precursor: S11: dissolving polyvinyl pyrrolidone or polyacrylonitrile in a mixed solvent of N,N-dimethylformamide and anhydrous ethanol to form a clear solution; S12: adding cupric acetate dihydrate and tetraethoxygermanium to the clear solution, and stirring to a homogeneous solution; S13: transferring the homogenous solution into a syringe for electrospinning, and peeling off the obtained Cu-Ge-PVP; S2: Preparation of CuGeO3 hollow nanotubes: S21: heating the Cu-Ge-PVP to 200° C. and baking it in an air atmosphere to obtain a Cu-Ge-PVP precursor; S22: heat-treating the Cu-Ge-PVP precursor, wherein the heat-treating process comprises: heating the Cu-Ge-PVP precursor at a heating rate of 1°C / min, heating the temperature to 350°C for the first time, and keeping the temperature for the first time, and then heating the Cu-Ge-PVP precursor to 500-700°C for the second time at a rate of 1°C / min after the heating, and obtaining CuGeO3 hollow nanotubes after the second heating; In the step S11, the average molecular weight of the polyvinyl pyrrolidone is 360,000, the mass concentration of polyvinyl pyrrolidone in the clear solution is 12%, and the average molecular weight of the polyacrylonitrile is 150,000; In the step S11, the molar ratio of N,N-dimethylformamide and anhydrous ethanol is (1-2): 1; In the step S12, the molar ratio of cupric acetate dihydrate to tetraethoxygermanium is 1:1; In step S21, the temperature is increased in a stepwise manner, including: increasing the temperature of the Cu-Ge-PVP to 100°C, keeping it warm for 2 hours, then increasing the temperature to 150°C, keeping it warm for 5 hours, then increasing the temperature to 170°C, keeping it warm for 5 hours, and finally increasing the temperature to 200°C; the baking time is 24 hours.
2. The method for preparing CuGeO3 hollow nanotubes according to claim 1, characterized in that: In step S13, the electrospinning step includes: injecting the homogenized solution into a plastic syringe, equipped with a No. 7 stainless steel needle, placing a receiving aluminum foil on a receiver 15 cm below the needle, and pushing at a speed of 1 mL h -1 , voltage was 15 kV, and electrospinning was performed.
3. The method for preparing CuGeO3 hollow nanotubes according to claim 1, characterized in that: In the step S13, the mass concentration of polyvinyl pyrrolidone in the homogeneous solution is 9-13%.
4. The method for preparing CuGeO3 hollow nanotubes according to claim 1, characterized in that: In the step S22, the temperature of the second heating is 500°C, and the time of the first insulation and the second insulation is 3 hours.
5. A CuGeO3 hollow nanotube, characterized in that: The CuGeO3 hollow nanotubes are prepared by the preparation method described in any one of claims 1-4.
6. An application of CuGeO3 hollow nanotubes, characterized in that: The application includes applying the CuGeO3 hollow nanotubes described in claim 5 to negative electrode materials of lithium-ion batteries.
Citation Information
Patent Citations
Contractive inner-structure-adjustable mesoporous inorganic salt nanotube material, preparation method therefor and application thereof
CN105375028A
Gas sensor and mebber using metal oxide nanofibers including nanoscale catalysts and multichannel, and manufacturing method thereof
KR1020190097755A
KR20190024300A